Some Points in the Treatment of Lead Ores in Missouri - C. P. Williams (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1877)
THE lead-bearing area of Missouri has been subdivided, geographically, into the Southeastern, the Central, and the Southwestern